Wrong-site, wrong-procedure, and retained foreign object events in out-of-hospital settings: analysis of closed medico-legal complaints in Canada (2012–2021) - Hajjaj, Omar I.; Zaslow, Joanna; Sherif, Reem E.; Héroux, Diane L.; Mimeault, Richard E.; Fortier, Jacqueline H.; Garber, Gary E. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Surgical sentinel events (SSEs) are serious safety incidents associated with significant patient harm and medico-legal consequences for healthcare teams and institutions. SSEs include wrong-site surgeries, wrong procedures, and unintentional retention of foreign objects. SSEs occur in hospitals and out-of-hospital operating spaces (physician offices or ambulatory surgical centres). It is unclear how the resource constraints and workflow differences of an out-of-hospital setting contribute to SSEs. Methods We conducted a retrospective review and descriptive content analysis of all out-of-hospital SSEs reported to the Canadian Medical Protective Association (CMPA) between 2012 and 2021. Medico-legal files, medical records, and peer expert opinions were analyzed to identify the contributing factors to out-of-hospital wrong-site, wrong-procedure, and retained-object SSEs. Results A total of 276 medico-legal complaints involved a wrong-site, wrong-procedure or retained-object SSE, of which 24 (24/276; 9%) occurred out of hospital. Only twenty of these out-of-hospital complaints were included in the qualitative content analysis. We identified five main contributing factor categories to out-of-hospital SSEs. These categories included (1) incomplete preoperative verification, (2) inadequate intraoperative surgical counts, (3) insufficient review of patient medical records, (4) surgery performed without the necessary resources, and (5) administrative errors or office disorganization. Half of the complaints were assigned more than one contributing factor. The majority of out-of-hospital SSEs (19/20; 95%) resulted in an unfavourable outcome for the operating physician and most (18/20; 90%) required additional healthcare resources to resolve or mitigate the consequences of the SSE. Conclusions Recognizing the contributing factors to an out-of-hospital SSE enables targeted improvements in facility protocols to support patient safety. Some factors identified in this dataset overlap with hospital-based contributing factors previously identified in literature (incomplete preoperative verification and inadequate surgical counts), whereas other novel factors are associated with the practice environment of an out-of-hospital setting (resource constraints, office disorganization). Addressing the identified contributing factors may mitigate the risk of SSEs in all facilities.